Evidence of Validity and Reliability of the Flexibility Scale in Mexican Youth - Palacios, Jorge (2021)
The purpose of this study was to analyze validity and reliability of the scores obtained with the Scale of the Flexibility (Melgoza y Díaz-Guerrero, 1990) in a sample of Mexican youth. The scale was tested in a sample of 309 young people between 14 and 24 years old, in México City and Metropolitan Area. Confirmatory factor analysis showed a three-factor structure: kindness, complacency and behavioral adaptation. Particularly kindness (β = .325, p < .001) and behavioral adaptation (β = .245, p < .001) predicted personal efficiency. The scale score has an internal consistency index of .85 (95 % CI = .83- .87). The usefulness of the results for the evaluation of flexibility and personality traits in young people is analyzed, as well as the implications for future research on ethnopsychology.